Design And Fabrication Of A 3d Printed Thyroid Phantom For Radiation Dosimetry - Alssabbagh, Moayyad Mazen (2018)
Estimation of internal and external radiation dose from SPECT/CT procedures depends mainly on calculations of Medical Internal Radiation Dose (MIRD) methods. Currently, there is no dynamic thyroid phantom with a precise geometrical shape which can simulate the biokinetics of the radiopharmaceuticals in the thyroid. The goal of this study was to design and fabricate a three-dimensional (3D) dynamic thyroid phantom for dosimetry and image quality evaluation. Nine 3D printing materials were evaluated in terms of elemental composition, mass attenuation coefficients, CT numbers and mass density, where The Energy Dispersive X-ray Spectroscopy (SEM-EDS) machine.